2012
DOI: 10.1029/2012ja017536
|View full text |Cite
|
Sign up to set email alerts
|

Can a halo CME from the limb be geoeffective?

Abstract: [1] The probability for a halo coronal mass ejection (CME) to be geoeffective is assumed to be higher the closer the CME launch site is located to the solar central meridian. However, events far from the central meridian may produce severe geomagnetic storms, like the case in April 2000. In this work, we study the possible geoeffectiveness of full halo CMEs with the source region situated at solar limb. For this task, we select all limb full halo (LFH) CMEs that occurred during solar cycle 23, and we search fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…The primary link between a geomagnetic storm and a CME is the out of the ecliptic component (Bz) of the interplanetary magnetic field (Gonzalez et al, 1994;Zhang et al 2007;Gopalswamy 2008;Echer et al 2008aEcher et al , 2008bEcher et al , 2013Cid et al 2012). Echer et al (2008a) conclusively showed that for all 90 major (Dst < −100 nT) storms that occurred during cycle 23, it was the Bz component that was responsible for the storms (some people have thought that it was possible that the IMF By component was also important).…”
Section: Cmes and Geomagnetic Stormsmentioning
confidence: 96%
“…The primary link between a geomagnetic storm and a CME is the out of the ecliptic component (Bz) of the interplanetary magnetic field (Gonzalez et al, 1994;Zhang et al 2007;Gopalswamy 2008;Echer et al 2008aEcher et al , 2008bEcher et al , 2013Cid et al 2012). Echer et al (2008a) conclusively showed that for all 90 major (Dst < −100 nT) storms that occurred during cycle 23, it was the Bz component that was responsible for the storms (some people have thought that it was possible that the IMF By component was also important).…”
Section: Cmes and Geomagnetic Stormsmentioning
confidence: 96%
“…Halo CMEs are commonly associated with energetic flares and are frequently geoeffective. However, we note that halo CMEs launched from regions close to the solar limb during Solar Cycle 23 were never very geoeffective (Cid et al, 2012). To be strongly geoeffective, the CME source has to be close to the central meridian.…”
Section: Morphology and Statisticsmentioning
confidence: 96%
“…According to study by Gopalswamy et al (2009b), almost ten percent of large geospace storms are caused by CMEs that originate close to the limb of the Sun. In such cases, the ICME sheath is typically the primary driver of the storm (see also Huttunen et al 2002), but cases have been reported where clear ejecta signatures upstream of the Earth and geomagnetic activity have been associated with limb CMEs (e.g., Schwenn et al 2005;Cid et al 2012;. For example, the CME studied by was initially heading toward the STEREO-B, but it deflected in the heliosphere and arrived at the Earth instead, which was located about 35°away from the STEREO-B at that time.…”
Section: Characteristics and Examples Of Cme/icme Deflectionmentioning
confidence: 99%